A 3D printable dynamic nanocellulose/nanochitin self-healing hydrogel and soft strain sensor. (1st September 2022) - Heidarian, Pejman; Gharaie, Saleh; Yousefi, Hossein; Paulino, Mariana; Kaynak, Akif; Varley, Russell; Kouzani, Abbas Z.
Abstract: Presented here is the synthesis of a 3D printable nano-polysaccharide self-healing hydrogel for flexible strain sensors. Consisting of three distinct yet complementary dynamic bonds, the crosslinked network comprises imine, hydrogen, and catecholato-metal coordination bonds. Self-healing of the hydrogel is demonstrated by macroscopic observation, rheological recovery, and compression measurements. The hydrogel was produced via imine formation of carboxyl methyl chitosan, oxidized cellulose nanofibers, and chitin nanofibers followed by two subsequent crosslinking stages: immersion in tannic acid (TA) solution to create hydrogen bonds, followed by soaking in Fe III solution to form catecholato-metal coordination bonds between TA and Fe III . The metal coordination bonds were critical to imparting conductivity to the hydrogel, a requirement for flexible strain sensors. The hydrogel exhibits excellent shear-thinning and dynamic properties with high autonomous self-healing (up to 89%) and self-recovery (up to 100%) at room temperature without external stimuli. Furthermore, it shows good printability, biocompatibility, and strain sensing ability. Graphical abstract: Unlabelled Image